2003
DOI: 10.1124/jpet.102.044040
|View full text |Cite
|
Sign up to set email alerts
|

The Thyrotropin-Releasing Hormone (TRH) Hypothesis of Homeostatic Regulation: Implications for TRH-Based Therapeutics

Abstract: The functions of thyrotropin-releasing hormone (TRH) in the central nervous system (CNS) can be conceptualized as performed by four anatomically distinct components that together comprise a general TRH homeostatic system. These components are 1) the hypothalamic-hypophysiotropic neuroendocrine system, 2) the brainstem/midbrain/spinal cord system, 3) the limbic/cortical system, and 4) the chronobiological system. We propose that the main neurobiological function of TRH is to promote homeostasis, accomplished th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 30 publications
2
65
0
2
Order By: Relevance
“…TRH has also been identified in both the CNS (Gary et al, 2003) and the immune system (Kamath et al, 2009) as a homeostatic regulator, or 'normalizer' of dysregulated physiologic systems, a property of increasing relevance in the pharmacotherapy of neurodegenerative disorders.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 4 more Smart Citations
“…TRH has also been identified in both the CNS (Gary et al, 2003) and the immune system (Kamath et al, 2009) as a homeostatic regulator, or 'normalizer' of dysregulated physiologic systems, a property of increasing relevance in the pharmacotherapy of neurodegenerative disorders.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Nevertheless, clinical trials of TRH and TRH analogs have already demonstrated positive effects in many CNS disorders (Gary et al, 2003;Kelly, 1995), with a good safety record (Kubek and Garg, 2002).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations